Constructing Bibliographic Relationships of Journal Collections through FRBR and DOI - Huei-Chu Chang (Jiàoyù zīliào yǔ túshūguǎn xué, 2015)
The study adopts citation checking and content analysis method. First of all, the study organizes the bibliographic relationships among journals, and continue to induct journal sample with three complex relations: rename, split, merge. Using MARC21 as its description format, the study analyzes elements necessary for constructing bibliographic relationships among journals, and compare it to the current kernel elements needed for journal registering, DOI. With the above method, this research goes on to examine the pros and cons of the current way of constructing bibliographic relationships, that is, adopting the essential metadata of national journal registration; then, to further explore the feasibility of carrying out applying recognition code and constructing the bibliographic relationships of journals simultaneously. The goal is to draw on the concept of supply chain and advance the identification and construction of bibliographic family to information processing upstream; so as to increase its efficiency by alleviating the burden of managing library journals and enhancing the connection between individual journals.